2015
DOI: 10.1111/jnc.13395
|View full text |Cite
|
Sign up to set email alerts
|

Neurological dysfunctions associated with altered BACE1‐dependent Neuregulin‐1 signaling

Abstract: Inhibition of BACE1 is being pursued as a therapeutic target to treat patients suffering from Alzheimer’s disease because BACE1 is the sole β-secretase that generates β-amyloid peptide. Knowledge regarding other cellular functions of BACE1 is therefore critical for the safe use of BACE1 inhibitors in human patients. Neuregulin-1 (Nrg1) is a BACE1 substrate and BACE1 cleavage of Nrg1 is critical for signaling functions in myelination, remyelination, synaptic plasticity, normal psychiatric behaviors and maintena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 230 publications
1
41
0
Order By: Relevance
“…To identify which neuronal protease may mediate DR6 shedding, neuronal cultures were used. The partial DR6 cleavage by ADAM10 behaves similar to other ADAM10 substrates, such as APP, which are also partly cleaved by ADAM10 and partly by other proteases, including the b-secretase BACE1 (Hu et al, 2016;Kuhn et al, 2016). While membranetype 1 matrix metalloprotease (MT1-MMP) was suggested as a DR6 protease in tumor cells (Tam et al, 2004;DeRosa et al, 2008), lentiviral knockdown of MT1-MMP did not alter DR6 shedding in neurons ( Fig EV1).…”
Section: Resultsmentioning
confidence: 66%
“…To identify which neuronal protease may mediate DR6 shedding, neuronal cultures were used. The partial DR6 cleavage by ADAM10 behaves similar to other ADAM10 substrates, such as APP, which are also partly cleaved by ADAM10 and partly by other proteases, including the b-secretase BACE1 (Hu et al, 2016;Kuhn et al, 2016). While membranetype 1 matrix metalloprotease (MT1-MMP) was suggested as a DR6 protease in tumor cells (Tam et al, 2004;DeRosa et al, 2008), lentiviral knockdown of MT1-MMP did not alter DR6 shedding in neurons ( Fig EV1).…”
Section: Resultsmentioning
confidence: 66%
“…It is suggested that these phenotypes are partly attributed to neuregulin-1 (Nrg1) signaling, which is known to regulate various brain functions through its actions on glutamatergic, GABAergic, and dopaminergic synapses [see updated review in (Mei and Nave, 2014) for more detailed discussion on the role of Nrg1 in synaptic function]. BACE1-dependent Nrg1 signaling is required for normal myelination during development, remyelination after injury, and maintenance of muscle spindles [see recent review by (Fleck et al, 2012; Hu et al, 2015)]. Impaired neuronal migration is due to abrogated cleavage of Sema3A-mediated CHL1 cleavage by BACE1 (Barao et al, 2015; Hitt et al, 2012; Kuhn et al, 2012; Zhou et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological concentrations of Aβ (in pM range) have been shown to facilitate synaptic plasticity [65] and BACE1 deficiency will cause a remarkable reduction in Aβ. Such a loss of physiological levels of Aβ may also lead to synaptic deficits.BACE1 deficiency alters synaptic plasticity in relation to neuregulin-1 cleavage: An alternative possibility is that the synaptic dysfunctions in BACE1-null mice may arise from abnormal processing of substrates other than APP, i.e., neuregulin-1 (Nrg1) [6668]. Nrg1 has a plethora of functions in the central and peripheral nervous systems, which include regulation of myelination, radial and tangential neuronal migration of glutamatergic and GABAergic neurons, and synaptic plasticity [69].…”
Section: Effects Of Bace1 On Synaptic Functionsmentioning
confidence: 99%